DETERMINAN RISK FACTOR WICH INFLUENCE OCCURENCE PREEKLAMPSI IN KABUPATEN BANYUMAS - Fajarsari, Dyah; Prabandari, Fitria (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Pre-eclampsia-eklamsia has shifted bleeding as the main cause of maternal mortality. Therefore, early diagnosis of pre-eclampsia is an introductory rate of eclampsia, as well as handling should be implemented to reduce Maternal Mortality Rate (MMR) and infant (IMR). Based on data from the Health Department Banyumas, 2014, AKI in Banyumas reached 118 cases per 100 thousand live births and is ranked third in the province of Central Java, or as many as 33 cases. From some cause eklamasi and bleeding into a sizeable contributor figures are respectively 14 and 5 cases. Objective research is to analyze the influence jointly the risk factors that influence the incidence preeklampsi include age, parity, preeklampsi history, family history preeklampsi, twin pregnancy, the diseaseprior to pregnancy, childbirth interval and BMI. This type of research is analytic survey with a retrospective case control approach. The population in this study were pregnant women with pre-eclampsia in five health centers with the highest number of pre eclampsia in Banyumas within the last 3 months. The sample in this study using the technique of total sampling of 60 pregnant women who are diagnosed Pre eclampsia as the case group and 60 respondents normal pregnant women. Analysis of data to analyze the effect of risk factors that affect the incidence preeklampsi using logistic regression analysis. The results of the risk factors that influence the incidence of pre-eclampsia were age (Ï: 0,009), parity (Ï: 0,000), a history of pre-eclampsia (Ï: 0,016), a family history of pre-eclampsia (Ï: 0.008), history of disease (Ï: 0,008 ) and IMT (Ï: 0,000).The strength of the relationship of the risk factor is a history of pre-eclampsia (OR: 63,487)Â Â Keywords: Risk Factors, Pre eclampsia